Implementasi Pembelajaran Berbasis Project Based Learning dan Case Method terhadap Kepuasan Belajar Mahasiswa - Pratiwi, Mirza Ayunda; Hidayat. R, Wahyu (Universitas Negeri Yogyakarta, 2024)
Effective teaching is crucial for enhancing learning quality in higher education, particularly at Universitas Maritim Raja Ali Haji. This study examines the impact of Project-Based Learning (PJBL) and the Case Method (CM) on student satisfaction. Using a survey method, questionnaires were distributed to 366 respondents, selected based on the Isac and Michael table with a 5% margin of error. PJBL and CM served as independent variables, while student satisfaction was the dependent variable. Data were analyzed using multiple linear regression, Pearson correlation, and validity and reliability tests with Cronbach's Alpha. Findings indicate a significant positive relationship between PJBL (r = 0.688) and CM (r = 0.639) with student satisfaction. Together, these methods contributed 49.3% to overall student satisfaction. These results highlight the effectiveness of PJBL and CM in improving student learning experiences and educational quality at Universitas Maritim Raja Ali Haji.Keywords: Project Based learning, Case Method, Study Satisfaction, Active Learning